PENGARUH CITRA MEREK, HARGA DAN KUALITAS PEMBELIAN TERHADAP KEPUTUSAN PEMBELIAN - Ida Abdul Gopar; Dhevi Tri Utami Nurhidayati (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to determine the effect of brand image on purchasing decisions on consumers of MSME central Zabannia, Effect of price on purchasing decisions on consumers of MSME central Zabannia, Effect of product quality on purchasing decisions on consumers of MSME central Zabannia. The research method used in this study is the quantitative method. While the approach used in this research is to use descriptive analysis using the results of questionnaire data that has been distributed to 93 respondents. The population used in this study were all users of MSME products from central Zabannia Pusat.Based on the results of the t test that has been carried out, it can be concluded that brand image has a significant and positive influence on purchasing decisions with a brand image significance value of 0,047 <0,05 and t value (2,015) > t table (1,98698), price has no effect significant and positive on purchasing decisions with a price significance value of 0,015 > 0,05 and a value of t count (2,471) < t table (1,98698), and product quality has a significant and positive influence on purchasing decisions with a significance value of product quality 0,000 < 0 ,05 and the value of t arithmetic (4,913) < t table (1,98698).